Psychotherapeutic group intervention for traumatized male refugees using imaginative stabilization techniques: a pilot study in a German reception center - Zehetmair, Catharina; Kaufmann, Claudia; Tegeler, Inga; Kindermann, David; Herpertz, Sabine; Herzog, Wolfgang; Nikendei, Christoph (Frontiers in psychiatry, 2018)
Background. Due to persecution, human rights violations and armed conflicts, the prevalence of post-traumatic stress disorder (PTSD) is high in refugee populations. Previous studies indicate that trauma-focussed treatments are highly effective in treating PTSD in refugees. However, these approaches rely on the stability of the therapeutic setting, treatment continuity, and safe housing. Although early treatment of PTSD is recommended, these requirements are not met in reception centers. Therefore, we conducted a pilot study to examine the effect of imaginative stabilization techniques derived from psychodynamic psychotraumatology therapy for the early stabilization of traumatized refugees in a reception center. Methods. From May 2017 to April 2018, 86 imaginative stabilization group therapy sessions have taken place. A sample of 43 out of 46 traumatized refugees completed self-report questionnaires assessing PTSD, depression and anxiety symptoms prior to attending open imaginative stabilization group therapy sessions. Furthermore, participants filled in self-report questionnaires on distress and emotional state (valence/ arousal/ dominance) before and after each session. After having participated in four consecutive sessions, a sub-group of 17 participants completed a follow-up assessment of PTSD, depression and anxiety symptoms. Follow-up interviews were conducted with 25 participants two weeks after their last session attendance to explore self-practice habits post intervention. Results. The pre-post-intervention comparison of scores indicated a significant reduction of distress (z = -3.35, p < .001, r = -.51) and an improvement of affective reports for valence (z = -4.79, p < .001, r = -.82) and dominance (z = -3.89, p < .001, r = -.59), whereas arousal scores were not affected. We found a significant reduction of anxiety symptoms (z = -2.04, p < .05, r = -.49), whereas PTSD and depression scores remained unchanged. Follow-up interviews revealed that 80% of the participants continued to practice the imaginative stabilization techniques after redistribution to other accommodation. Conclusion. The results indicate that imaginative stabilization techniques are a promising and feasible approach to treat refugees in unstable reception center settings. In regular imaginative stabilization group therapy sessions, we were able to reduce the participants’ distress and anxiety symptoms while strengthening their internal resources and increasing their emotional stability.
Gesehen am 06.12.2018